2002
DOI: 10.1159/000058354
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability and Internal Consistency Reliability of the Nottingham Health Profile in Dementia Patients

Abstract: Background: Few studies have evaluated subjective health status in dementia patients. Objectives: The aim of the study was to determinate the feasibility, acceptability and internal consistency reliability of measuring subjective health status in dementia patients with the Nottingham Health Profile (NHP). Design: The French version of the NHP was administered to 145 dementia patients and their proxies (family caregivers and formal caregivers). Measures: The refusal rate, type of administration and time for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 15 publications
5
33
1
Order By: Relevance
“…This was an inter-rater reliability study: the Nottingham Health Profile (NHP) scores of elderly persons with mild to moderate dementia (MMSE > 9) were compared with NHP scores as provided by two different proxies for each subject. For dementia patients, test-retest validity of the NHP has already been analysed in a previous study (Bureau-Chalot et al, 2002) and was found to range from moderate to excellent according to the dimension. Family proxies for the present study were chosen among people who knew and saw the patient most regularly.…”
Section: Methodsmentioning
confidence: 93%
“…This was an inter-rater reliability study: the Nottingham Health Profile (NHP) scores of elderly persons with mild to moderate dementia (MMSE > 9) were compared with NHP scores as provided by two different proxies for each subject. For dementia patients, test-retest validity of the NHP has already been analysed in a previous study (Bureau-Chalot et al, 2002) and was found to range from moderate to excellent according to the dimension. Family proxies for the present study were chosen among people who knew and saw the patient most regularly.…”
Section: Methodsmentioning
confidence: 93%
“…However, several studies suggested that awareness of deficit may vary greatly across individuals [34] , and metamemory function is maintained in the early stages of AD [36,37] . In the previous studies, self-assessment questionnaires for physical and psychological symptoms were administrated to mild to moderate dementia patients [38,39] . In addition, a recent study reported that self-rated questionnaires could differentiate nondemented from demented individuals, especially when of mild severity [34] .…”
Section: Discussionmentioning
confidence: 99%
“…74 The validity of the Nottingham Health Profile, SF-12 and EQ-5D for people with dementia is also questionable. [75][76][77] The content, format and instructions of HRQoL instruments must be appropriate to people with dementia, given their cognitive difficulties. By definition, generic measures are not necessarily designed in a way that makes them easy for a person with dementia to complete.…”
Section: Generic Measuresmentioning
confidence: 99%